Profiling of phenolic compounds and their antioxidant and anticancer activity in pandan (Pandanus amaryllifolius Roxb.) extracts from different locations of Malaysia. - Ghasemzadeh, Ali; Jaafar, Hawa Z. E. (BioMed Central, 2013)
Background Phytochemicals and antioxidants from plant sources are of increasing interest to consumers because of their roles in the maintenance of human health. Most of the secondary metabolites of herbs are used in a number of pharmaceutical products.